A case of type II Mirizzi syndrome treated by simple endoscopic means. Issue 10 (8th October 2018) - Cheung, Fu Ho Victor; Mak, Chi Chuen Clarence; Chu, Wai Yin; Fan, Ning; Lui, Ka Wing
Abstract: Mirizzi syndrome is an uncommon complication of chronic cholelithiasis. Advancement in radiological modalities and minimally invasive surgery has led to improved pre-operative diagnoses and more laparoscopic cholecystectomies. But for unsuitable surgical candidates, endoscopy can be the definitive treatment. In this case, we present a 67-year-old man with type II Mirizzi syndrome treated by simple endoscopic means.